2009
DOI: 10.1002/adem.200900127
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of a Silorane‐Based Composite System to Bone

Abstract: This work was to analyze by Weibull statistics the shear bond strength of a low‐shrink Silorane‐based composite system to bone. The etching abilities of the adhesives were investigated by scanning electron microscopy. Results suggest that an effective and reliable bond to bone could be achieved by the Silorane‐based composite system, showing the potential of this system to be used as a bone cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although initially developed for use in dentistry, silorane-based cements have been recognized for their potential applications in orthopaedics. 13 , 14 We have developed a silorane-based biomaterial (SBB) intended for use as an orthopaedic cement, suitable for weight-bearing applications, local delivery of antibiotics, grafting for bone lesions, voids or defects, and augmentation of various implants. 15 Unlike the silorane-based dental cements, which require ultraviolet (UV) light for polymerization, this SBB uses a dual-cure initiation system composed of both a light photoinitiation and chemical catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Although initially developed for use in dentistry, silorane-based cements have been recognized for their potential applications in orthopaedics. 13 , 14 We have developed a silorane-based biomaterial (SBB) intended for use as an orthopaedic cement, suitable for weight-bearing applications, local delivery of antibiotics, grafting for bone lesions, voids or defects, and augmentation of various implants. 15 Unlike the silorane-based dental cements, which require ultraviolet (UV) light for polymerization, this SBB uses a dual-cure initiation system composed of both a light photoinitiation and chemical catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] It was also shown that a silorane-based dental composite can effectively bond to bone. 21 In order to begin to develop better bone cements, we analyzed the effect of silorane-based resins on bone cell function in vitro and in vivo. One aim of the present study was to analyze the effect of silorane-based resin on bone cell proliferation, differentiation, and mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…It can also delineate local effects from systemic factors (Meghji et al, 1998). We previously developed a critical size defect (CSD) organ culture model (Wu and Watts, ).…”
Section: Introductionmentioning
confidence: 99%